Gps solution for active queue management using android platform - Liu, Yu Yao (2021)
This proposed project proposes an active queue management system in multiple location integrated with GPS (Global Positioning System) Android mobile application. This project introduces a model for effective management of queue in different locations using GPS as a medium. Since most of the existing software on the market does not manage tickets in an efficient way and does not provide route planning function, this proposed project aims to solve the aforementioned problems by develop an Android mobile application which check travel time for user before taking ticket, allows user to delay ticket in case of not enough queue time and help user to plan route on multiple places as well as navigate user to the location. The application developed will help public to save their precious time by utilising the waiting time into doing something more worthy such as part of queue time. Since queueing in different locations is considered as a optimisation problem, several algorithms are reviewed to tackle the problem, such as brute force method, nearest neighbour algorithm, and branch and bound algorithm. Four tickets management applications, namely QueueBee, powerQ, WaveTec and QLess are reviewed to understand both strengths and weaknesses of existing application on current market. A comparison table is constructed to compare their functions to visualise differences between them. From the table, the proposed application can identify which function to focus on. Tools used to develop the project is Android Studio with Google Firebase as database of this project. This project uses prototype developing methodology which the application will improve on every deployment. If user has at least one ticket taken, system can generate an optimised route using branch and bound method. User can also send swap ticket request to next user. If the user accepts the request, both tickets will be swapped. The final deliverable of this project would be a multi-location queue management Android application with GPS supported.